Indonesian Learning Media: Setting, Making, Searching, Select-ing, Quality checklists and procedures, and Data Analysis and Synthesis - Ghufron, Syamsul; Markub, Markub; Tudy, Ida Gauran (Universitas Negeri Semarang, 2023)
Online learning during the pandemic has an impact on the development of the use of learning media. This study aims to describe the Indonesian language learning media in elementary schools. This research is classified as a systematic literature review with the following procedure: (1) setting the background and objectives, (2) making research questions, (3) searching for literature, (4) selecting criteria, (5) quality check-lists and procedures, and (6) data analysis and synthesis. The database used to search for literature is Google Scholar. Searching the data using the keywords